An ABCC8 nonsense mutation causing neonatal diabetes through altered transcript expression - Flanagan, SE; Dũng, VC; Houghton, JAL; De Franco, E; Ngoc, CTB; Damhuis, A; Ashcroft, FM; Harries, LW; Ellard, S (Galenos Publishing House, 2017)
The pancreatic ATP-sensitive K+ (K-ATP) channel is a key regulator of insulin secretion. Gain-of-function mutations in the genes encoding the Kir6.2 (KCNJ11) and SUR1 (ABCC8) subunits of the channel cause neonatal diabetes, whilst loss-of-function mutations in these genes result in congenital hyperinsulinism. We report two patients with neonatal diabetes in whom we unexpectedly identified recessively inherited loss-of-function mutations. The aim of this study was to investigate how a homozygous nonsense mutation in ABCC8 could result in neonatal diabetes. The ABCC8 p.Glu747* was identified in two unrelated Vietnamese patients. This mutation is located within the in-frame exon 17 and RNA studies confirmed (a) the absence of full length SUR1 mRNA and (b) the presence of the alternatively spliced transcript lacking exon 17. Successful transfer of both patients to sulphonylurea treatment suggests that the altered transcript expression enhances the sensitivity of the K-ATP channel to Mg-ADP/ATP. This is the first report of an ABCC8 nonsense mutation causing a gain-of-channel function and these findings extend the spectrum of K-ATP channel mutations observed in patients with neonatal diabetes.